Critical Study of Amina Wadud's Thought in the Issue of Inheritance - Fauzan Zenrif; Syabbul Bachri (De Jure: Jurnal Hukum dan Syari'ah, 2023)
This study aims to examine the main arguments presented by Amina Wadud on inheritance in her book "Quran and Women" and evaluate the validity of her arguments. The scope of this research will include an analysis of Wadud's method of interpreting the Quran as outlined in the book Quran and Women which influenced her thoughts on Islamic inheritance and a critical study of her thoughts. This research is a type of qualitative research with a critical study approach. The results of the study show that a critical study of Wadud's thinking shows that she generalizes the 2:1 provision on the shares of men and women which actually only applies in certain cases. In addition, Wadud's demands for reinterpretation cannot be done without adequate interpretive science tools. Science explains that justice need not be interpreted as equality. There are two categories of justice, according to Aristotle: commutative justice and distributive justice. So that there can be no justification for questioning the Quran's just inheritance allocation. Furthermore, the provisions in the inheritance verse in the Quran are qath'i provisions so there is no justification for doing ijtihad which is presumptive (dzanny) in a reassuring text (qath'i). In addition, Wadud's thoughts are also considered less specific and do not provide a real format for how the redistribution she proposes. Therefore, Wadud's rereading in terms of inheritance is considered incomplete or incomprehensive of the Qur'an.